Analisis Perilaku Pengguna Dan Karakteristik Parkir On-Street Citimall Gorontalo - Sri Ameliana Saman; Heryati Heryati; syafriyani syafriyani (JARI: Journal of Architecture, Research and Innovation, 2026)
On-street parking facilities are crucial elements in urban transportation systems. However, the imbalance between spatial capacity and high demand volume frequently causes traffic delays. This study aims to analyze the operational characteristics and behavioral architecture dynamics at the parking facility in front of Citimall Gorontalo. The research uses a mixed-methods approach (qualitative and quantitative) through structured observation, interviews, and documentation. Spatial data analysis applies a behavioral mapping approach encompassing place-centered mapping, person-centered mapping, and physical trace. The results indicate that the parking area is divided into four segments. Segment 2 recorded the highest accumulation rate, exceeding normal capacity (overcapacity). This is driven by user preferences oriented towards the closest distance to the main gate. This concentration triggers search circulation, which reduces through-traffic speed and causes bottlenecks during peak hours. In conclusion, circulation performance degradation is heavily influenced by user behavioral adaptation, operator activities, and the absence of geometric markings.